2009
DOI: 10.2460/ajvr.70.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of extracorporeal shock wave treatment on experimentally induced osteoarthritis in middle carpal joints of horses

Abstract: OBJECTIVE-To assess the clinical, biochemical, and histologic effects of extracorporeal shock wave therapy (ESWT) in the treatment of horses with experimentally induced osteoarthritis (OA). ANIMALS-Twenty-four 2- to 3-year-old horses without evidence of lameness. PROCEDURES-OA was induced arthroscopically in 1 middle carpal joint of each horse. Fourteen days after induction of OA, horses were treated with a sham ESWT probe (placebo; n = 8), polysulfated glycosaminoglycan (PSGAG) administered IM every 4 days fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 14 publications
0
37
0
Order By: Relevance
“…Several studies reported positive effects of ESWT in osteoarthritis of different joints in animals [37][38][39][40][41]. The exact mechanism of shockwave therapy was still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported positive effects of ESWT in osteoarthritis of different joints in animals [37][38][39][40][41]. The exact mechanism of shockwave therapy was still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It improved the rats' walking ability [23]. It signiicantly improved the lameness degree in horses [24].…”
Section: Right Kneementioning
confidence: 92%
“…It can treat such diseases as chronic tendinopathies, nonunion of long bone fracture, and early stage of avascular necrosis of the formal head [22]. Moreover, ESWT difused to the treatment of OA in animals [23,24]. It improved the rats' walking ability [23].…”
Section: Right Kneementioning
confidence: 99%
“…ESWT has shown effectiveness in many orthopedic disorders including soft tissue tendinopathy and non-union of long bone fractures [12,13]. In addition, many studies including ours reported positive effects of ESWT in various arthritic joints in animals [14][15][16][17][18]. Our previous studies demonstrated that ESWT is chondroprotective in the initiation of OA changes of the knee [19,20], and induces regression or retardation of established OA changes of the knee in rats [21].…”
Section: Research Papermentioning
confidence: 99%